Strengthening the Values of Compliance and Discipline by Teachers Guidance Counseling in Overcoming the Disciplinary Behavior of Class IX Students at State Junior High Schools 2 Larangan Pamekasan - Ni’matul Mukaromah; Sitti Khotijah (Interpersonal: Jurnal Bimbingan Konseling Islam, 2025)
Every school certainly has applicable regulations and rules, school rules and regulations aim to guide student behavior to create an orderly, safe, peaceful, conducive and disciplined school living environment. Disciplinary students commit violations of the rules such as being late, sleeping in class, skipping class, incomplete ceremonial attributes, which can cause harm to themselves, and will even receive sanctions or punishment. From here, BK teachers play a role in strengthening the values of obedience and discipline as well as accompanying, helping and supervising students to behave in a disciplined manner. The research focus in this thesis is: 1) What is the cause of the discipline of class IX students at SMPN 2 Prohibition? 2) How is BK Teachers Strengthening the Values of Compliance and Discipline in Overcoming the Disciplinary Behavior of Class IX SMPN 2 Students Prohibited? The research method used by researchers is a descriptive qualitative approach. Descriptive qualitative is presenting problems or findings in the field according to what is happening. The data collection technique in this study used observations, interviews and documentation. The results of this research are: (1) The disciplinary causes of class IX SMPN 2 Prohibition students are internal (intrinsic) factors, namely a feeling of laziness and indifference in lessons. Next are factors from outside (extrinsic), namely factors from family and the influence of friends and the surrounding environment. (2) In strengthening the values of obedience and discipline, BK teachers overcome the discipline of class IX SMPN 2 Prohibition students by identifying problems, providing warnings, advice, guidance, calling, home visits (home visits), calling parents, and collaborating with teachers or homeroom teacher. (3) The impact of strengthening carried out by BK teachers provides changes to students such as changes in behavior and increased self-awareness.